Public Attitudes Towards Consent When Research is Integrated Into Care—Any “Ought” from All the “Is”? - Morain, Stephanie R. (Hastings Cent Rep, 2021)
Research approaches that integrate learning into ongoing clinical activities offer the potential to accelerate the generation of knowledge to improve the health of individuals and populations. Yet, integrating research into clinical care raises difficult ethical and regulatory questions. Multiple empirical studies have explored patients’ and public attitudes toward approaches to consent for pragmatic research. Open questions remain, however, regarding the appropriate role of the resulting empirical data in resolving normative debates. We propose that data on acceptability or informed preferences should be prioritized; suggest caution regarding the weight given to majority viewpoints; and identify circumstances when empirical data can be overridden. We argue that empirical data bolster normative arguments that alterations of consent should be the default in pragmatic research; waivers are appropriate only when the pragmatic research would otherwise be impracticable and also has sufficiently high social value. We conclude with suggestions for additional work to guide policy decisions.